The Role of NOD-like Receptors in Recognition of Pathogen-associated Molecular Patterns of Infectious Pathogens and in Development of Inflammation - A.Ye. Abaturov; A.P. Volosovets; Ye.I. Yulish (Zaslavsky O.Yu., 2013)
The review described the mechanisms of inflammasomes formation.